April May June July : a novel [large type] - Hart, Alison B. (Thorndike Press large print top shelf., 2024)
"April, May, June, and July Barber don't have much in common anymore. An upcoming family wedding will place the four siblings in the same room for the first time in years. But shortly before, when April spots their father, who went missing while serving overseas a decade ago, their reunion becomes entirely more complicated. While the siblings' search for the truth about their father forces them back into each other's lives, it also intensifies their private dramas. April loves her husband, but seeks excitement outside their marriage. May had big dreams for the future, but she's still stuck living at home. June is eager to marry her girlfriend, so why does she need a drink at every wedding-related event? And then there's baby brother July, whose unrequited love for his straight roommate has him more confused than ever. Confronting the past together, April, May, June, and July will find not only answers about their father, but new romance, hope, and understanding as they learn to embrace the beauty of their shared history"--